¿Patriotas contra realistas?: Participación y experiencias de los sectores populares durante la guerra en el espacio sur-andino, 1809-1825 - Davio, Marisa (2021)
The objective of this article is to analyze the participation and mobilization of the popular sectors, the vast majority of which were part of both patriotic and royalist troops in the revolutionary war within the southern-Andean space. From the study of different cases, the aim is to understand the experiences of the war and the degree of identification of these sectors with the political causes at stake during that process. Thus, the reasons why the members of both troops or the summoned militias fought is questioned, as well as the political concepts used in their speeches to identify themselves with the struggle in favor of a given cause and the fees requested to remain in the military corps.